Penatalaksanaan Holistik Hemoroid Interna Grade II pada Pria Usia 42 Tahun Melalui Pendekatan Kedokteran Keluarga di Wilayah Kerja Puskesmas Rawat Inap Sukaraja - Retno Mareintika; Ernawati, Tutik (CV. Jasa Sukses Abadi, 2025)
Hemorrhoids are submucosal swellings in the anal canal, consisting of venous plexuses, small arteries, and dilated areolar tissue. in 2019, approximately 4.4% of the global population suffered from hemorrhoidal disease. Data from WHO in 2017, the number of hemorrhoids cases reached 230 million people. In 2017, the global incidence of hemorrhoids increased to 54%. In Indonesia, based on the Basic Health Research (Riskesdas) data, it is estimated 2030, the number of individuals suffering from hemorrhoids will reach 21.3 million. The objective of this study is to identify internal and external risk factors, as well as clinical problems in patients, and to apply Evidence-Based Medicine (EBM) in the family doctor services for these patients. The management of patients was conducted based on a patient-centered, family-focused, and community-oriented problem-solving framework. Primary data were obtained through autoanamnesis, physical examination, and home visits, while secondary data were gathered from patients' medical records. The evaluation was based on a holistic diagnosis from the beginning to the end of the study, both qualitatively and quantitatively. Patient Mr. T, 42 years old, had a main complaint of bulging protruding mass from his anus that is exacerbated with defecation and bowel movements. accompanied by bleeding for the past week. The patient was concerned about the worsening of the condition. Clinically, the patient was diagnosed with Grade II Internal Hemorrhoids. A holistic management approach was implemented, including an intervention using a poster as a media. The diagnosis and management of this patient were carried out holistically and comprehensively, based on several theories and current research. During the behavior change process, the patient has reached the trial stage.